SOCIAL INTELLIGENCE AND PROFESSIONAL COMPETENCE IN ENHANCING LEARNING CREATIVITY IN ISLAMIC RELIGIOUS EDUCATION AT IBNU CHALDUN UNIVERSITY JAKARTA - Kartika, Ika; Fauzan Ginanjar, Taufiq; Abdul Gofur, Huliman; Meliani, Fitri; Paramansyah, Arman; Saepudin, Saepudin (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: In the context of increasing demands for quality education, it is essential to understand the factors that contribute to enhancing students' learning creativity, particularly in Islamic Religious Education (PAI). As the educational landscape evolves, fostering skills such as social intelligence and professional competence in students is vital to their academic success and personal growth. Purpose: This study aims to find out and analyze the influence of social intelligence and professional competence on student learning creativity in Islamic religious education learning at Ibnu Chaldun University Jakarta. Method: This study uses a quantitative research method with survey techniques to answer the hypothesis test that has been formulated. The respondents amounted to 160 students, and the sampling technique used was a random sampling technique. Questionnaires on social intelligence, professional competence, and learning creativity were validated by the product-moment correlation formula, and reliability was measured by the Alpha Cronbach formula. Hypothesis testing using the SEM PLS analysis application. Result: The results of the study show that social intelligence has a direct and significant effect on learning creativity, and professional competence has a direct positive and significant effect on learning creativity. Social intelligence has a direct and significant influence on professional competence. So that to increase learning creativity, it can be done through increasing social intelligence and professional competence. Conclusion: From the results of the study, it was concluded that social intelligence has a direct and significant effect on learning creativity, professional competence has a direct positive and significant effect on learning creativity, and social intelligence has a direct and significant effect on professional competence.